Auditory evoked potential in normal hearing and sensorineural hearing loss among Malay and Chinese adults / Ibrahim Amer Ibrahim - Ibrahim Amer , Ibrahim (2019)
Neural plasticity in the human brain is defined as the change of the structure, function, and organization of neurons/nerve cells due to new experiences. Despite the factors causing hearing loss being reported in literature, the exact role of these factors and the changes in the auditory neuron process remains unclear. There is also a dearth of studies on the auditory evoked brain potential in multiple ethnic groups. This research addresses neuronal plasticity, which correlates hearing and speech before and after the onset of hearing impairment in two ethnic groups. This study will play a vital role towards the design and development of efficient hearing aids/implants, speech recognition software, and in the rehabilitation of patients suffering from hearing loss. This study intends to elucidate the differences in the cortical auditory evoked potential (CAEP) between subjects with normal hearing and sensorineural hearing loss (SNHL). It will also explore the differences and limitations in the CAEP in two ethnic groups (Malay and Chinese) with/without SNHL. This work is limited in its ability to classify CAEP signal based on stimuli sounds for ethnic groups (Malay and Chinese). The aims of this study could be realized by investigating the impact of different auditory stimuli (Pure Tone and Consonant-Vowel) on the electrophysiological neural representation (waveform morphology, latency, and amplitude) of the CAEP components. This investigation was conducted on Malay and Chinese normal hearing volunteers, as well as those suffering from sensorineural hearing loss. This study presents accurate and novel formulated indices for classifying brain auditory responses and human hearing abilities. A classification algorithm was used to classify the CAEP responses evoked from multiple auditory stimulus for normal hearing subjects and SNHL patients in the case of both ethnicities. The results indicated that the SNHL alters the human central auditory system in an adult brain. We concluded that the SNHL subjects elicited greater amplitude with prolonged latencies throughout the majority of the CAEP components when the subjects were exposed to multiple auditory stimuli. The contradiction in the CAEP components (amplitudes and latencies) and classification accuracy between subjects with SNHL and normal subjects was attributed to the neurological deficit in the SNHL patients. The findings suggested that the MMN (MisMatch Negativity), as a diagnostic tool for the hearing-impaired population, was limited (unclear) relative to other CAEP responses. N1, P2, and N2 were the dominant CAEP component in variation and change of the amplitude and latency, reporting the maximum appearing percentages. We also confirmed that there is a higher probability that the Chinese subject groups suffer from hearing impairment at a rate higher than the Malay group. However, the Chinese subjects exhibited excellent distinguishing ability in recognizing auditory stimuli relative to the Malay group.